The Water Quality Monitoring of Semuong River in Protected Forest Register 39, Gunung Doh Village, Tanggamus Regency, Lampung Province - Yudithia Wirda Ariani; Abdullah Aman Damai; Nidya Kartini (Jurnal Perikanan dan Kelautan, 2021)
Good water quality is very important to support the sustainability of the organisms that live in it. The location of the Semuong River which is close to mining and human activities such as settlements will generally cause environmental problems such as water quality degradation. The research was to determine the Samuong river water quality based on its physical and chemical parameters. This research was conducted from November to December 2019 with sampling locations in the Semuong River and analysis done at the Environmental Laboratory of PT. Unilab Perdana. Water sampling was carried out at five stations, namely left, right, main, upstream and downstream Lunik. The results of the measurement of samples were compared with the quality standards stipulated by Lampung Regional Regulation No. 11 of 2012 and analyzed using the STORET method. The results showed that The values of several parameters were exceeded the threshold for class III water quality standards, namely BOD and COD. Based on STORET index in the first sampling has a total score of -4 which is categorized as lightly polluted, the second sampling has a total score of -16 which is categorized as moderate pollution, the third sampling has a total score of -40 which is categorized as heavily polluted, and the forth sampling has a score of 0 which is categorized as not polluted.